Caracterización de un material compuesto matriz termoestable reforzado con fibra de guadua (2017)
The present document will show the different tests carried out at a Composite material with polyester resin matrix and reinforced with Guadua Different procedures were carried out for the elimination of Lignin, in order to verify the influence on the behavior of the material and They obtained different results in their qualitative and quantitative properties Where methods and tests such as Van Soest are used, stress tests And SEM analysis. The composite material by means of a mold process Open and using different percentages of fiber at 10%, 15% and 20% guadua In the polymer In the uninstallation section, tests were performed on the guadua treated with Different methods to decrease their percentage of lignin, it was identified that the Less harmful method is the mixture of acetic acid and sodium chloride with which You can improve or maintain the properties of guadua for your post Processing and inclusion in the compound. We work in guadua in strips Longitudinal brushes for easy manipulation. After the facts De-lignification processes were followed with a milling of these strips and a Screening by selecting an appropriate size with which the material was created Compound; In addition, a fiber analysis study was carried out by means of From a scanning microscope (SEM) where it was found that the chlorite process Sodium and acetic acid is the one that produces better fiber bonding.